2018
DOI: 10.18203/2320-6012.ijrms20184034
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus associated acute throat infection among children presented to a tertiary care hospital

Abstract: Background: Staphylococcus infection remains one of the most common bacterial infections that cause high rate of morbidity and mortality in children and adults. This study was aimed to find the prevalent age group and type of Staphylococcus strain among the children presented with sore throat to a tertiary care hospital.Methods: A retrospective study was done by analyzing the medical records of children (less than 10 years of age) who presented to the outpatient Paediatric department with sore throat and confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Our study was divided into 5 age groups (0-5), (6)(7)(8)(9)(10)(11)(12)(13)(14)(15), , (41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60) (40) (2022) conducted a study in Jaipur (India) & reported UTIs to be present predominantly in females then males, (60.7%) UTI in females and (39.3%) UTIs in males. A similar study was conducted by Banerjee, et al, (32) (2017) West Bengal (India) in their study they also found that females more prone to UTI then in males, they found (73.33%) UTIs in females and (26.67%) UTIs in males.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study was divided into 5 age groups (0-5), (6)(7)(8)(9)(10)(11)(12)(13)(14)(15), , (41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60) (40) (2022) conducted a study in Jaipur (India) & reported UTIs to be present predominantly in females then males, (60.7%) UTI in females and (39.3%) UTIs in males. A similar study was conducted by Banerjee, et al, (32) (2017) West Bengal (India) in their study they also found that females more prone to UTI then in males, they found (73.33%) UTIs in females and (26.67%) UTIs in males.…”
Section: Discussionmentioning
confidence: 99%
“…The higher incidence rate of UTIs among females is attributed to the anatomical structure of urinary tract of females & sexual activity. Bhargava et al, (40) conducted a study in Jaipur (India) 2022 und found gram negative bacteria to predominantly cause UTIs as compared to gram positive bacteria, (67.2%) were gram negative and (10.8%) were gram positive bacteria. A similar study was conducted by Sabharwal et al, (41) New Delhi (2015) in their study they also found (82.9%) gram negative bacteria and (17%) gram positive bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…CoNS are generally considered nonpathogenic, and their presence in clinical material has been interpreted as contamination by normal microbiota present in the mucous membranes of the oral cavity and upper respiratory tracts. However, there are few reports on CoNS in cultures from throat infections, but these studies were mostly in children, and the role of CoNS as causative agents should be further investigated [122][123][124].…”
Section: Pharyngitis Throat Infectionmentioning
confidence: 99%